Kajian Bentuk dan Makna Simbolis Ornamen pada Masjid Kontemporer di Indonesia - Rahma Samroatul Fuadah; Saila Arzaqina (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study examines the forms and symbolic meanings of ornaments in contemporary mosques in Indonesia as a manifestation of the fusion between Islamic values, local traditions, and modernity. Utilizing a qualitative-descriptive research method through comprehensive literature review, the study analyzes various ornaments in several contemporary mosques in Indonesia, such as the Azizi Mosque in Tanjung Pura, the Cheng Hoo Mosque in Surabaya, and the Al Osmani Mosque. The findings reveal that the ornamentation in Indonesia's contemporary mosques exhibits rich diversity, including geometric, organic, calligraphic, and floral motifs, each with its own uniqueness and characteristics. From a symbolic perspective, these ornaments serve not only as aesthetic elements but also as mediums imbued with philosophical, spiritual, and social values, reflecting the harmony between tradition and modernity. This research highlights how the architecture of contemporary mosques in Indonesia has successfully developed a distinct identity through ornamentation that is not only visually appealing but also deeply meaningful and relevant to the present context. These findings contribute significantly to the understanding of the development of mosque architecture in Indonesia and serve as a reference for designing future contemporary mosques.